The concept of hypothetical flows - Буйвол, В.М. (Proceedings of National Aviation University (archive), 2004)
The basic statements of the concept of hypothetical flow have been formulated. This concept transforms task about free surface motion to solution of system of nonlinear differential equations relatively modes of surface's deformations. This concept transforms task about free surface motion to solution of system of nonlinear differential equations relatively modes of surface's deformations. This concept may be used for investigation of motion of both thin cavities and vacuities in medium with properties of real medium.